(untitled) (Innovative professional education, 2023)
Methodological bases of the development of e-learning courses for blended learning in professional (vocational) education institutions are considered. It is noted that for the effectiveness of education it is important to use a complex approach and ensure interaction between students and teachers. It is also important to adapt the course to the needs and capabilities of students and to ensure the quality of the educational material and technical support of the course. Designing an effective course can improve the quality of students knowledge and contribute to their success.